A compact synchrotron‐based transmission X‐ray microscope. (24th January 2014) - Chen, Yu‐Sheng; Chen, Huang‐Han; Li, Tsong‐Tse; Ong, Edwin; Lim, Jun; Margaritondo, Giorgio; Hwu, En‐Te; Hwu, Yeukuang
<x xml:space="preserve">Abstract</x> A compact transmission X‐ray microscope has been designed and implemented based on a cylindrical symmetry around the optical axis that sharply limits the instabilities due to thermal mechanical drift. Identical compact multi‐axis closed‐loop actuation modules drive different optical components. The design is modular and simplifies the change of individual parts, e.g. the use of different magnification and focusing devices. This compact instrument can be easily transported between laboratory and synchrotron facilities and quickly put into operation. An automated alignment mechanism simplifies the assembly of different modules after transportation. After describing the design details, the results of the first tests are presented.